Relationship between Predetermined Maintenance Interval and Maintenance Performance - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (Trans Tech Publications, 2016)
Currently, lack of preventive measure is the problem that implicates poor maintenance outcome. Scheduled maintenance is claimed as a maintenance strategy to tackle the problem. However, the effectiveness of scheduled maintenance can be greatly influenced by the length of predetermined maintenance interval. Thus, this paper aims to study the relationship between length of predetermined maintenance interval and maintenance performance. The literature review identifies the length of predetermined maintenance interval as an importance characteristic of scheduled maintenance strategy. A quantitative approach is adopted and carried out through questionnaire survey. Subsequently, descriptive analysis and correlation analysis are used to analyse the collected data. Then, research result demonstrates that the length of predetermined maintenance interval is significantly correlated to the maintenance performance. The length of predetermined maintenance interval must be considered in maintenance planning and execution. The research recommends continuous monitoring or regular inspection of building systems and components to identify their condition and update the length of predetermined maintenance interval regularly. Consequently, the effective maintenance execution helps to avoid systems failure occurs and optimises maintenance performance.